Towards a Methodology of Intersectionality: An Axiom-Based Approach - Hillsburg, Heather (Atlantis)

(untitled) (Mount Saint Vincent University, 2013)
This article maps the emergence of intersectional feminist theory and explores the difficulties translating this theory into a methodology. To address these tensions, this article proposes three axioms that centre on things the researcher must avoid when conducting intersectional research and explores how these axioms can alleviate current tensions within intersectional research.